Update on Focal Cortical Dysplasia and the Imaging of Epilepsy - Gadde, Judith A.; Schwartz, Erin S. (Journal of Pediatric Neurology, 2018)
Epilepsy affects up to 1 in 1,000 children annually. While it is increasingly recognized that forms of epilepsy may have genetic origins, congenital and acquired structural abnormalities of the brain parenchyma are common causes of seizures. Among the most difficult etiologies to diagnose are focal cortical dysplasias, which will be discussed along with their unique imaging features. While magnetic resonance (MR) imaging is the mainstay of epilepsy imaging, magnetoencephalography (MEG) and positon emission tomography (PET) have become increasingly recognized as adding value to the presurgical evaluation of medically refractory epilepsy. More recently, PET/MR hybrid scanning is gaining popularity.
Keywords: epilepsy; focal cortical dysplasia; imaging; magnetoencephalography; positon emission tomography; magnetic resonance